2016
DOI: 10.1093/mnras/stw2819
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical modelling of the galactic bulge and bar: the Milky Way's pattern speed, stellar and dark matter mass distribution

Abstract: We construct a large set of dynamical models of the galactic bulge, bar and inner disk using the Made-to-Measure method. Our models are constrained to match the red clump giant density from a combination of the VVV, UKIDSS and 2MASS infrared surveys together with stellar kinematics in the bulge from the BRAVA and OGLE surveys, and in the entire bar region from the ARGOS survey. We are able to recover the bar pattern speed and the stellar and dark matter mass distributions in the bar region, thus recovering the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

63
327
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 321 publications
(396 citation statements)
references
References 130 publications
(203 reference statements)
63
327
6
Order By: Relevance
“…Specifically, the SIDM halo has responded more to the imposed potential than the CDM halo and this has driven the two profiles to a very similar end state. We only begin to see the formation of an SIDM core within ∼1 kpc, which is similar to the Milky Way core size measured in Portail et al (2017). The Extended Disk runs, which impose a less severe potential, have maintained something closer to the original differences, with SIDM beginning to roll off toward a core within ∼3 kpc, but the differences between the SIDM and CDM are less severe than in the DM-only case (which disagree at 5 kpc).…”
Section: Milky Way Halossupporting
confidence: 56%
“…Specifically, the SIDM halo has responded more to the imposed potential than the CDM halo and this has driven the two profiles to a very similar end state. We only begin to see the formation of an SIDM core within ∼1 kpc, which is similar to the Milky Way core size measured in Portail et al (2017). The Extended Disk runs, which impose a less severe potential, have maintained something closer to the original differences, with SIDM beginning to roll off toward a core within ∼3 kpc, but the differences between the SIDM and CDM are less severe than in the DM-only case (which disagree at 5 kpc).…”
Section: Milky Way Halossupporting
confidence: 56%
“…First, we increase the resolution of the model by a factor of 10, using a variant of the resampling algorithm presented in Dehnen (2009) because originally only ∼ 650 particles lay within 600 pc from the Sun. Second, the radial dispersion of the outer disk unconstrained in Portail et al (2017) and is found after M2M fitting to be σ U = 44 km s −1 , larger than the observed ∼ 36 km s −1 (see Section 2.2). Large radial dispersion in the disk is the result of orbits with large epicycle motions around their guiding centers.…”
Section: Dynamical Model Of the Galaxymentioning
confidence: 70%
“…Recently, Portail et al (2017) presented the first nonparametric dynamical model of the entire bar region. Using the Made-to-Measure (M2M) method (De Lorenzi et al 2007;Portail et al 2015), they adapted the particle weights of a self-consistent N-body model of the Galaxy in order to match data from numerous surveys.…”
Section: Dynamical Model Of the Galaxymentioning
confidence: 99%
See 1 more Smart Citation
“…Careful dynamical modeling by Portail et al [20] has recently uncovered a central shortfall of 2 × 10 9 M ⊙ of "missing matter" which may help account for the 100 km/s motion of stars within the central ≃ 120 pc of the galaxy [32][33][34] and which we aim to examine in the context of the near spherical soliton potential that we predict here. By using pulsars spread over a wide range of Galactocentric radius we may detect the radial dependence of pulsar timing ampliude on the dark matter density, beyond current limits claimed in [35] and pulsar binary resonance [36].…”
Section: Discussionmentioning
confidence: 92%